Gender Equality in E-Sports: A Transitivity Analysis in Saloni Pawar's Achievement Posts - Wibowo, Saraswati Syifannisa; Lililacs , Admin (Lililacs Journal, 2022)
This study aims to analyze the transitivity analysis system in the comments column in the post of Saloni Pawar's achievements to see gender equality in E-sports. The data source was obtained from Saloni Pawar's posts on Instagram. In this study, the researcher uses the theory of Systemic Functional Linguistic (SFL), which is a linguistic approach that aims to understand how a text forms its meaning in a context, using Halliday's (1985) Transitivity Analysis system. This study uses a qualitative method. The data from this study are words, phrases, and sentences in the comments column to see the meaning implied in each comment that is intended for female gamers in the posting of Saloni Pawar's achievements as female gamers and professional gamers in e-sports. The results of this study indicate that during Saloni Pawar's career in E-sports, this have been more positive comments than negative ones directed at her. The researcher found that the material process in which the most dominant condition was type of support comments. Each of them has their own way of expressing their opinion to Saloni Pawar as a female gamer